The influence of the scaffolding approach on critical thinking skills and student collaboration on mathematics learning - Retno Ayu Trisnawati; Ali Mahmudi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Students' critical thinking abilities and collaboration skills still need to be considered. To overcome the low critical thinking skills and encourage collaboration skills, innovative learning is needed by applying a scaffolding approach when mathematics learning takes place. Apart from critical thinking skills, students' collaboration skills must also be considered. This research aims to: 1) analyze the effect of the scaffolding approach on critical thinking skills, and 2) analyze the effect of the scaffolding approach on students' collaboration skills. This type of research is a pre-experiment with a one-group pretest-posttest design. The sample in this study was students in class VIII-C of SMP Negeri 1 Yogyakarta, totaling 32 students. Data collection techniques include tests, questionnaires, and observations. The analysis used is a paired t-test. The research results obtained are 1) learning with a scaffolding approach shows a significant difference in critical thinking abilities and collaboration skills as viewed from the pre-test and post-test results, and 2) learning mathematics with a scaffolding approach can improve students' critical thinking abilities and collaborative skills.